The Preliminary Ruling 242-IP-2015 of the Andean Court of Justice - Indacochea Jauregui, Juan Manuel (Revista Tribuna Internacional, 2018)
The Preliminary Ruling 242-IP-2015, on the tactile mark consisting in the surface of the bottle "Old Parr", is the first decision rendered by an international court about tactile marks. The purpose of this paper is to explain the application of the main registration requirements to new types of Trademarks, in the light of the criteria explained in the aforementioned Preliminary Ruling. It also aims to analyze the previous jurisprudential development, concerning the active legitimacy of administrative authorities to optionally request preliminary rulings. That is the first question –or subject– addressed in the above-mentioned Preliminary Ruling since the interpretation was requested by an Administrative Authority –Office– of Colombia.